SMARTBUY dataset - Andersson, Karl; Gavalas, Damianos (Luleå University of Technology, 2019)
The dataset represents a compilation of user interaction data generated by users who participated in the project's pilot activities in Patras, Greece. Data was generated by users in the SMARTBUY app and includes information about users, stores, product categories, professions, and events.

The dataset comprises the following data:
- users: user account data for the Patras pilot users
- occupation: all possible occupations that the pilot users could choose from
- stores: stores which participated in the Patras pilot
- sel_products_cat: products uploaded to the SMARTBUY platform by retailers
- events: geo-stamped and time-stamped descriptions of a user interaction event (for instance, "user_id 67 rated product_id 722 with rating 4 at location x1 at datetime y1", or "user_id 91 denoted product_id 78 as favorite at location x2 at datetime y2")
- event_types: all possible event types captured by the SMARTBUY platform ('Product searches', 'Product views', 'Featured product', 'Products near you views', 'Product photos browsed', 'Product ratings', 'Clicks on Read More button to read product reviews', 'Clicks on Open map button', 'Clicks on Send this info by email button', 'Products denoted as Favorite')

Privacy-sensitive information such as user names, retailer owner names and store names and keywords searched are anonymized.

Datasetet representerar en sammanställning av användarinteraktionsdata som genererats av användare som deltog i projektets pilotverksamheten i Patras, Grekland. Data genererades av användare i SMARTBUY-appen och omfattar information om användare, butiker, produktkategorier, yrken och evenemang.

Datasetet innehåller följande data:
- användare: användarkontodata för Patras pilotanvändare
- yrke: alla möjliga yrken som pilotanvändarna kan välja mellan
- butiker: butiker som deltog i Patras-piloten
- sel_products_cat: produkter som laddas upp till SMARTBUY-plattformen av återförsäljare
- händelser: geo-stämplade och tidsstämplade beskrivningar av en användarinteraktionshändelse (till exempel "user_id 67 rankade produkt_id 722 med betyg 4 på plats x1 vid tidpunkt y1", eller "user_id 91 betecknade produkt_id 78 som favorit på plats x2 vid datetime y2 ")
- event_types: alla möjliga händelsetyper som fångats av SMARTBUY-plattformen ('Produktsökningar', 'Produktvyer', 'Utvalda produkter', 'Produkter nära dig visningar', 'Produktfoton bläddrade', 'Produktbetyg', 'Klicka på Läs Mer knapp för att läsa produktrecensioner, "Klick på knappen Öppna karta", "Klicka på Skicka denna information via e-postknappen", "Produkter betecknade som favorit")

Integritetskänslig information som användarnamn, detaljistägarnamn och butiksnamn och sökord som sökts har anonymiserats.
SMARTBUY dataset
Keywords: occupation; SMARTBUY; SMARTBUY; product_cat; produktkategori; users; användare; stores; butiker; events; evenemang; Information technology; Informationsteknik; Computer and Information Sciences; Data- och informationsvetenskap (datateknik)